2005
DOI: 10.1002/cncr.21179
|View full text |Cite
|
Sign up to set email alerts
|

Malignant insulinoma

Abstract: BACKGROUNDMalignant insulinoma occurs in a few patients with insulinoma. Due to the small sample of patients, there are little data regarding their clinical manifestation as well as the preferred treatment modalities. The aims of the current study were to summarize the National Institutes of Health experience during the last two decades and to conduct a critical review of the current literature.METHODSThe authors identified 10 patients with metastatic insulinoma.RESULTSThe patients presented with four patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(63 citation statements)
references
References 38 publications
(34 reference statements)
3
56
0
4
Order By: Relevance
“…This observation is in contrast to the better response to diazoxide in adults, before surgery (7,8,9).…”
Section: Discussionmentioning
confidence: 61%
“…This observation is in contrast to the better response to diazoxide in adults, before surgery (7,8,9).…”
Section: Discussionmentioning
confidence: 61%
“…Patients with a malignant insulinoma should undergo formal pancreatic resection. An aggressive approach is recommended in the presence of metastatic disease; if appropriate, surgery should be combined with lymph node dissection and/or hepatic tumor reduction [7, 8, 37]. Of our 4 patients, 3 are alive, and 1 survived for more than 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Danforth et al [38] demonstrated a median disease-free survival after curative resection of 5 years, with a recurrence rate of 63%. After initial surgical resection, the biology of the tumor, rather than any treatment modality, was most likely the major determinant of the long-term survival [8]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present knowledge regarding PET treatment comes, for the most part, from small, retrospective, uncontrolled studies. Moreover, many reports involve highly selected patients (surgical series of resected patients [6,7], oncological series of mainly metastatic patients [8,9] and series focused on benign functioning neoplasms [10,11]), thus making it difficult to understand the relative frequency of different treatments and to compare their results.…”
Section: Introductionmentioning
confidence: 99%